An investigation of beta enolase as a histological marker of rhabdomyosarcoma. Issue 8 (August 1984) - Royds, J A; Variend, S; Timperley, W R; Taylor, C B
Abstract : Sections from 21 tumours diagnosed as primary or metastatic rhabdomyosarcoma were stained for alpha and beta enolase. The cases were subdivided into embryonal and alveolar subtypes (38% and 62%, respectively). Positive cytoplasmic staining for alpha enolase was seen in all but one case, and cytoplasmic staining for beta enolase was seen in some cells in 18 of the 21 cases (86% of the total, 88% of the alveolar subgroup, and 85% of the embryonal subgroup). No cells stained positively for beta enolase in the control series of neuroblastomas, fibrosarcomas, Wilms' sarcomas, and an osteosarcoma. The results show that beta enolase is a sensitive marker of muscular differentiation in rhabdomyosarcoma.